Semecarpus euodiifolius - Hoo, P.K.; Tsen, S.; Damit, A.; Khoo, E.; Colin Ruzelion Maycock; Nilus, R.; Sabran, S.; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Semecarpus euodiifolius is uncommon and was recorded from eastern (Sandakan district) and western Sabah (Kuala Penyu, Beaufort, and Tenom). Most of the sites have been converted into palm oil plantation, except for Beaufort hill and Lumaku forest reserve (Tenom). Due to the land use change and forest fire, there is an estimated decline of 90% in extent of occurrence (EOO) and 67% in area of occupancy (AOO) across its range (based on GeoCAT reduction analysis) in 60 years. After this reduction, estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 8 km2. This decline in habitat and distribution is inferred to have caused a population loss of at least 90% over the last three generations. Decline is still continuing as one site of the species remains outside of a protected area. Hence, it is assessed as Critically Endangered. Semecarpus euodifolius is endemic to Sabah, Malaysia. It was recorded from Beaufort, Tenom, and Kuala Penyu in western Sabah and from the Sandakan district in eastern Sabah. Most of the sites has been converted into palm oil plantation, except for Beaufort hill and Tenom localities.